A Homeobox Transcription Factor UvHOX2 Regulates Chlamydospore Formation, Conidiogenesis, and Pathogenicity in Ustilaginoidea virens - Yu, Junjie; Yu, Mina; Song, Tianqiao; Cao, Huijuan; Pan, Xiayan; Yong, Mingli; Qi, Zhongqiang; Du, Yan; Zhang, Rongsheng; Yin, Xiaole; Liu, Yongfeng (Frontiers in Microbiology, 2019)
Rice false smut fungus (teleomorph: Villosiclava virens; anamorph: Ustilaginoidea virens) can generate chlamydospores and survive winter under field conditions. The chlamydospore is considered as an important infection source of the disease. However, little is known about the regulatory mechanism of the chlamydospore production. In this study, we identified a defective homeobox transcription factor (designated as UvHOX2) gene in a U. virens random insertional mutant B-766 that could not form chlamydospores. To confirm the regulatory function of UvHOX2, an Agrobacterium tumefaciens mediated transformation- and CRISPR/Cas9- based targeted gene replacement method was developed. The UvHox2 deletion mutants completely failed to produce chlamydospores, showed reduced conidia production and decreased virulence, and was hyper-sensitive to oxidative, osmotic, and cell wall stresses. We confirmed that UvHOX2 is located in the nuclei of U. virens, and the expression of UvHox2 was the strongest during the early stage of chlamydospore and conidium formation. Global transcription pattern of UvHOX2 was also determined by RNA-seq in this study, and several genes that might be down-stream of UvHOX2 regulation were identified. The results will better our understanding of the molecular mechanism of chlamydospore formation in U. virens as a model fungus.